Poisoning Resistance of Liquid GaPt Supported Catalytically Active Liquid Metal Solutions Model Systems - Wichmann, Christoph; Moritz, Michael; Wittkämper, Haiko; Hsieh, Tzung En; Frisch, Johannes; Bär, Marcus; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2024)
SiOx-supported liquid GaPt systems show remarkable catalytic activity and stability in lab-scale alkane dehydrogenation reactions. However, large-scale applications provide additional challenges, like the presence of catalyst poisons in the catalytic feed that strongly bind and block active sites. A common poison are sulfur traces, which tend to interact strongly with transition metals like Pt. Therefore, macroscopic GaPt alloy droplets with low Pt content (1 at. %) and nanoscopic GaPt particles were investigated during the exposure to thiophene as catalyst poison and organic sulfur source. The measurements were performed using X-ray photoelectron spectroscopy under ultrahigh vacuum and near-ambient pressure conditions. We observed the formation of a ∼2.5 nm Ga sulfide layer, in which Pt accumulates. Notably, we do not find the formation of Pt sulfides in the model systems. For higher temperatures (>650 K), the formed Ga sulfides dissolve into the liquid metallic Ga-matrix, resulting in a Ga sulfide-free gas/liquid interface. In reference measurements, it was shown that the pure Pt particles are poisoned by sulfur and Ga is not reactive toward the formation of sulfides. Pt seems to play a key role in the formation of Ga sulfides since particles only consisting of Ga show only minor sulfur deposits.
CRIS-Team Scopus Importer:2024-06-07